Monsters Among Us: Pets, Cuisine, and the Politics of Otherness. The Woman Who Cooked Turtles and the Cat-Eater - Mangani, Giulio (E|C, 2025)
The political practice of attributing a disgusting, criminal or monstrous eating habit to someone whom one wishes to keep at a distance or expel is as old as the world itself and is part of the strategies with which cultures establish their identity in relation to otherness. Taking a cue from Donald Trump’s accusation of pet predation against Haitian immigrants during the last electoral campaign, we will analyze two Italian cases framed by the media in the realm of horror and adopted in the right-wing narrative as markers of the impossibility of cohabitation: the homeless woman who secretly cooked turtles in Rome and the man caught publicly roasting a cat in Livorno. The purpose of this paper is to investigate the preconditions for the effectiveness of this theme in political discourse, along with the tensions that arise between marginal local food practices, which are prohibited but tolerated, and those attributed to immigrants, which are conversely stigmatized without exception.